Personalised immunotherapy strategies informed by single cell profiling in thyroid cancer: a mini review - Chen, Ruyu; Wang, Zhimin; Chen, Xueying; Huang, Yangling; Zhang, Fengnuan; Gao, Tianshu (Frontiers in Immunology, 2025)
Thyroid cancer (TC) is now among the fastest-growing solid tumours, yet therapeutic gains remain limited for poorly differentiated, anaplastic and medullary variants whose median survivals are measured in months. Once guided chiefly by histology and single-gene assays, immunotherapy is being reshaped by single-cell profiling, which exposes the cellular mosaics that arbitrate response and resistance. Dissection of more than 150–000 tumour- and immune-cell transcriptomes has uncovered follicular-like, partial EMT-like and dedifferentiated thyrocyte states embedded within ‘hot’ (CD8hi IFN-γhi), ‘cold’ (CD8lo) and ‘excluded’ (stroma-walled) immune niches; these phenotypes correlate with PD-1/LAG-3 expression, macrophage polarisation and radio-iodine refractoriness. Functional studies reveal that SPP1–CD44 and GAS6–AXL crosstalk licenses epithelial–mesenchymal transition while VSIG4+ macrophages blunt cytotoxic T-cell activity, collectively undermining checkpoint blockade. Spatial transcriptomics corroborates these insights, mapping PD-L1-high tumour islets millimetres from CXCL13-rich tertiary lymphoid structures, whereas CITE-seq quantifies actionable checkpoints and cytokine receptors across patient biopsies. Emerging therapeutics mirror this granular knowledge: combinatorial PD-1 + LAG-3 inhibition, CSF-1R-directed macrophage re-programming and TSH-receptor-targeted CAR-T cells are advancing through early-phase trials, while ex-vivo single-cell pharmacotyping aligns drug cocktails with an individual’s tumour ecosystem. Early lenvatinib-pembrolizumab or selpercatinib-nivolumab trials show ~40% ORR but grade-3 hypertension >60%, prompting staggered-start designs. These advances sharpen pathogenetic resolution, refine patient selection and accelerate translational pipeline design. By integrating single-cell biology, immunology and endocrine oncology, this review identifies diagnostic blind spots, spotlights drug-repurposing opportunities and charts a roadmap toward personalised immunotherapeutic strategies capable of improving outcomes across the diverse spectrum of thyroid cancer.